Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 925756 species occurrences available in GBIF matching the query: { "or" : [ "Country is Nigeria", "Country is Ghana", "Country is Cameroon", "Country is Liberia" ] } The dataset includes 925756 records from 630 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0008858-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences